Impact of the Economic Crisis on SMEs (Small and Medium-Sized Enterprises): A General Evaluation on SMEs in Turkey - Aktürk, Oktay (European Journal of Social Science Education and Research, 2014)
Liberalization taking place in the global capital and financial market in recent years and correspondingly the lack of adequate control mechanisms have caused economic crisis at global, regional and country level. While the crises have affected the overall economy, the greatest negative impact has been observed on SMEs. Considering the share of SMEs in total initiatives and employment in worldwide economy, it is seen that they are key points for economies. In this respect, the determination and analysis of the impact of economic crisis on SMEs are very important for a healthy economic development. Starting with this point, in ttis study, especially in the context of recent global crisis, a general assessment on economic crisis has been made and the position of SMEs in the economic structure, the effect of crisis on SMEs has been tried to put forward especially on the basis of Turkey. Several scientific studies and statistical data conducted on SMEs and economic crisis have been examined for this purpose.
Keywords: SME, crisis, 2008 crisis, stability, development.